Laparoscopic sterilization. - Mangel Leon, Teodoro (2015)
The Centre for Social Studies and Population at the University of Costa Rica, found through research conducted in 1971 on female sterilizations performed between 59 and 69, that there was a significant increase (from 836 cases in 1959 to 3,189 for 1969), but it is worth emphasizing that only 52.7% of the sterilizations carried out during this period were the direct type (salpingectomy) and in 51.4% of cases originated indication reasons doctor surgical (Health)